Activation induced cytidine deaminase: An old friend with new faces - Çakan, Elif; Gunaydin, Gurcan (Frontiers in Immunology, 2022)
Activation induced cytidine deaminase (AID) protein is a member of APOBEC family. AID converts cytidine to uracil, which is a key step for somatic hypermutation (SHM) and class switch recombination (CSR). AID also plays critical roles in B cell precursor stages, removing polyreactive B cells from immune repertoire. Since the main function of AID is inducing point mutations, dysregulation can lead to increased mutation load, translocations, disturbed genomic integrity, and lymphomagenesis. As such, expression of AID as well as its function is controlled strictly at various molecular steps. Other members of the APOBEC family also play crucial roles during carcinogenesis. Considering all these functions, AID represents a bridge, linking chronic inflammation to carcinogenesis and immune deficiencies to autoimmune manifestations.